ANALISIS HARGA MINIMUM LAYAK DI TINGKAT PETANI ATAS GABAH KERING PANEN (GKP) DAN BERAS DI DESA PAHANG ASRI KECAMATAN BUAY PEMUKA PELIUNG KABUPATEN OKU TIMUR - Sugeng Supriyanto (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2015)
The objectives of this study were to: (1) Calculate what is the minimum feasible price at the farmer level for dry rice harvest and rice in Pahang Asri Village, (2) Compare the minimum price with the actual price (market price) on the sales of dry milled grain and rice. This research was conducted in Pahang Asri Village, Buay Pemuka Peliung District, OKU Timur District. Determining the location was done purposively, from 13 villages in Kecamatan Buay Pemuka Peliung only Pahang Asri Village selected by the researcher to conduct a research on analysis of minimum price of rice and rice with the consideration that in the village the only village that has a village regulation ( Perdes) on rice yield management. Data collection at research location was conducted in March to June 2014 (Production data of planting season I, October 2013 - March 2014). The study found that the minimum average minimum rate at farmers' level for dry paddy harvest (GKP) is Rp.2.666 / kg and the minimum price is feasible at the farmer level on rice of Rp. 3.754, - / kg. The two minimum prices at the farmers' level are lower than the actual price of Rp 3,217, - per kg for dry harvest (GKP) and Rp. 6.434, - per kg for rice. There is a difference between the actual price and the appropriate minimum price at the farmer level of dry unhulled rice (GKP). In the Paired Samples Statistic table, the average actual price of dry paddy harvest (GKP) is Rp.3.217,11 / kg and for the minimum price of dry paddy harvested (GKP) is Rp.2.666 / kg. This indicates that the actual price of dry paddy harvest (GKP) is higher than the minimum price of dry paddy harvested (GKP).